Ecotoxicological effects of pig manure on Folsomia candida in subtropical Brazilian soils - Maccari A.P.* (2016)
© 2016.The effects of pig manure, from diets incorporating veterinary pharmaceuticals, on survival and reproduction of Folsomia candida were evaluated. Manures derived from the following diets: corn and soymeal (CS); 85% CS diet + 15% wheat meal (TR); CS diet + 100 ppm doxycycline + 50 ppm colistin + 2500 ppm Zn oxide (CSa); TR diet + 100 ppm doxycycline + 50 ppm colistin + 2500 ppm Zn oxide (TRa). Manures were tested in two subtropical soils representative of southern (Oxisol and Entisol). Despite the antibiotics no significant differences were found between the four manures within each soil. However, strong differences were found on the toxicity between soils. In Oxisol, LC50 values were around 100 m3 ha-1, and EC50 values around 80 m3 ha-1. In Entisol these were much lower, with LC50 values oscillating around 20 m3 ha-1 and EC50 values between 10-15 m3 ha-1. The observed toxicity on both soils was attributed to excess of nitrogen, Cu and Zn in the highest doses. The strong difference between soils could be explained by soil properties, namely CEC, organic matter, and clay contents that were lower in Entisol, indicating a poor ability to retain contaminants increasing their availability in soil. Results suggest that the application of these residues should be regulated not only using a volume-based criterion, but should incorporate data on soil properties, complemented by an ecotoxicological assessment.